Constitutions as Chains? On the Intergenerational Challenges of Constitution-Making - Konstantin Chatziathanasiou (Intergenerational Justice Review)
In this essay, I explore the ambiguity of the competition’s title “Constitutions as Chains”, and distinguish between two intergenerational challenges in constitution-making: the challenge of intergenerationally just constitutional provisions, and the challenge of creating a stable institution which is accepted by successive generations. I prioritise the latter. After contrasting classic ideas of Burke and Paine, I discuss different ways of addressing the challenge, such as the amendability of a constitution, eternity clauses or recurring constitutional assemblies. A flexible approach towards existing constitutional provisions, which is open to future developments, gets the nod. However, a need for empirical research remains.